Environmental function of the state in modern globalization processes - Гетьман, А. П. (Problems of legality, 2015)
The article notes that the globalization of the world and its current development in all areas, including environmental one − these are the real facts. The transformation of the respective roles of the state and, above all, ecological one, takes place under their influence. Its goal should be to subordinate the society to ecological imperative, transformation of the nature of the state with an absolute target and functional orientation of all the activities on the implementation of this imperative.